2020
DOI: 10.1177/1932296820918540
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Hypoglycemia: The Challenge Remains

Abstract: Hypoglycemia in inpatients with diabetes remains the most common complication of diabetes therapies. Hypoglycemia is independently associated with increased morbidity and mortality, increased length of stay, increased readmission rate, and increased cost. This review describes the importance of reporting and addressing inpatient hypoglycemia; it further summarizes eight strategies that aid clinicians in the prevention of inpatient hypoglycemia: auditing the electronic medical record, formulary restrictions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 61 publications
0
23
0
2
Order By: Relevance
“…Inpatient hypoglycemia is a prevalent and often preventable adverse event associated with increased morbidity and mortality, length of stay, readmissions, and health care expenditures. 1 , 2 , 3 , 4 , 5 , 6 Considering that most patients with diabetes are hospitalized for reasons other than glucose management, 7 , 8 situational unawareness of the near-term risk of iatrogenic hypoglycemia may result from competing medical priorities, lack of sufficient training in glycemic pattern recognition, 9 , 10 , 11 or other system factors. 12 Studies 13 , 14 , 15 have demonstrated practitioner inertia in adjusting glucose-lowering medications before hypoglycemic events or in response to antecedent hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatient hypoglycemia is a prevalent and often preventable adverse event associated with increased morbidity and mortality, length of stay, readmissions, and health care expenditures. 1 , 2 , 3 , 4 , 5 , 6 Considering that most patients with diabetes are hospitalized for reasons other than glucose management, 7 , 8 situational unawareness of the near-term risk of iatrogenic hypoglycemia may result from competing medical priorities, lack of sufficient training in glycemic pattern recognition, 9 , 10 , 11 or other system factors. 12 Studies 13 , 14 , 15 have demonstrated practitioner inertia in adjusting glucose-lowering medications before hypoglycemic events or in response to antecedent hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Changes in dextrose-containing fluids, tapering corticosteroid doses, disruption in parenteral nutrition or continuous tube feedings, mismatched timing of point-of-care blood glucose (BG) testing with insulin delivery and meal consumption, correctional scale overuse, and insulin stacking are just a few examples of the various factors that can influence the risk of iatrogenic hypoglycemia. 1 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, when blood glucose decreases to 70mg/dL (3.9mmol/L), cognitive dysfunction may occur; when blood glucose decrease to 54mg/dl (3.0mmol/L) and sustains for a long time, it may cause brain death [11] . Perioperative hypoglycemia, especially repeated and severe hypoglycemia, may negatively affect the health outcomes of the patients, leading to increased morbidity and mortality, length of stay, readmissions, and health care expenditures [9][10] . In addition, it may also bring about a huge socio-economic burden to the family and society as a whole [9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Hypoglycemia has been minimized through risk factor reduction with the use of clinical strategies including standardized reporting, order sets, and hypoglycemia protocols in addition to implementation of technological tools such as electronic medical records, continuous subcutaneous insulin infusion pumps, and continuous glucose monitoring technology with predictive scores and remote surveillance capability. 6 The cost of diabetes is currently accounting for almost $250 billion (one in four healthcare dollars spent in the United States). 7 It is estimated that hypoglycemia may add 31% to the overall cost for an inpatient stay, with the average cost of $4312 per admission.…”
Section: Introductionmentioning
confidence: 99%